Quantifying Glans Width Changes in Response to Preoperative Androgen Stimulation in Patients Undergoing Hypospadias Repair. Issue 6 (11th June 2022) - Mittal, Sameer; Eftekharzadeh, Sahar; Christianson, Sarah S.; Hyacinthe, Nathan; Tan, Connie; Weiss, Dana A.; Van Batavia, Jason; Zderic, Steve A.; Shukla, Aseem R.; Kolon, Thomas F.; Srinivasan, Arun K.; Canning, Douglas A.; et al.
Abstract : Purpose: Testosterone (T) administration prior to hypospadias surgery to increase glans size remains controversial. Understanding T's effect on glans width (GW) is essential to understanding its potential impact on surgical outcomes. We hypothesized that preoperative T in prepubertal boys significantly increases GW at the time of hypospadias surgery. Materials and Methods: Our single institutional database was queried to identify patients who underwent hypospadias surgery from 2016 to 2020, in which data for T administration and GW were available. Descriptive, nonparametric and categorical statistics were performed as indicated. Results: A total of 579 patients were eligible for analysis. Median age at surgery was 0.9 years (IQR 0.6–1.6). A total of 247/579 patients (42.7%) received T. The median GW at surgery was 15 mm (IQR 13–17). When comparing patients who had T administered to those who did not, we found a significant difference in GW at surgery (16 mm vs 14 mm, p <0.001). The median change in GW from the office to surgery was 4 mm for those receiving T vs 0 mm for those not receiving T (p <0.001). We identified a greater change in GW from preoperative to intraoperative measurements in patients who received 2 doses of T vs 1 dose (4 mm vs 2 mm, p <0.001). A histogram plot revealed the distribution of GW change at surgery. Conclusions: In our prospectively collected cohort of patients undergoing hypospadias surgery, we were able to quantitate the change in GW from preoperative T. Two doses of T resulted in a significant increase in GW vs 1 dose.